Introduction to Protein Structure - Brändén, Carl-Ivar Tooze, John (Garland Publishers, 1991)
This new edition gives an up-to-date account of the principles of protein structure, with examples of key proteins in their biological context, illustrated in colour to illuminate the structural principles described in the text.